2019
DOI: 10.1016/j.eimc.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Could human bocavirus be a causative agent of parotitis in children?

Abstract: Could human bocavirus be a causative agent of parotitis in children?¿Puede ser el bocavirus humano un agente causal de parotiditis en niños?Dear Editor,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…13 The association between HBoV, detected at the same frequency as that of HHV4, and parotitis is rare. However, according to Calvo et al, 14 HBoV was identified as a symptom of left parotitis, high fever, and dyspnea in a 17-month-old male infant, suggesting that it should be suspected as a cause of acute nonmumps parotitis in young children.…”
Section: Discussionmentioning
confidence: 99%
“…13 The association between HBoV, detected at the same frequency as that of HHV4, and parotitis is rare. However, according to Calvo et al, 14 HBoV was identified as a symptom of left parotitis, high fever, and dyspnea in a 17-month-old male infant, suggesting that it should be suspected as a cause of acute nonmumps parotitis in young children.…”
Section: Discussionmentioning
confidence: 99%
“…The association between HBoV, detected at the same frequency as that of HHV4, and parotitis is rare. However, according to Calvo et al [18], HBoV was identified as a symptom of left sinusitis, high fever, and dyspnea in a 17-month-old male infant, suggesting that it should be suspected as a cause of acute non-mumps parotitis in young children.…”
Section: Discussionmentioning
confidence: 99%